Ultrasonic Wave Characteristics of Arumanis Mangoes And Damage Arumanis Mangoes By Fruit Fly - Warji .; Rokhani Hasbullah (PERTETA, 2009)
The objective of this research was to study the ultrasonic wave characteristic at arumanis mangoesdamage caused by fruit fly. The ultrasonic characteristics that was used to sort the damaged mangoes fromthe normal mangoes were attenuation, velocity and moment zero power (Mo) number. Results showed thatmean attenuation coefficient of normal arumanis mangoes was 36.45 Np/m, mean velocity of ultrasonicwave was 518.19 m/s and Mo number was 4.58. The mean attenuation coefficient arumanis mangoeswhich damaged by fruit fly was 30.67 Np/m, mean velocity of ultrasonic wave was 731.72 m/s and Monumber was 6.40. Relation between the ultrasonic wave characteristic with arumanis mangoes damagecaused by fruit fly showed that attenuation coefficient of arumanis mangoes was increase but damagearumanis mangoes level was decrease, while Mo number was increase in parallel with increase of damagearumanis mangoes level. The ultrasonic wave velocities of arumanis mangoes didn’t show clear correlationwith damage arumanis mangoes level, as shown by from value of r2=0.01. Larva weight of inversely tovalue of attenuation coefficient, correlation of logarithm value r2=0.94. Correlation value of larva weight Mowith number was r2=0.38.Keyword : ultrasonic wave, arumanis mangoes, fruit fly, attenuation coefficient, Mo numberDiterima: 13 Maret 2008; Disetujui: 27 Oktober 2008